Purification and Immunological Evaluation of Protective Antigens of Outer Membrane Origin of Pasteurella Multocida Type 6:B - Mohamed, Ramlan (2000)
A study on the toxic effects of lipopolysaccharide (LPS) of Pasteurella multocida type 6:B in mice was conducted. In addition, the immunogenic potential of LPS as subunit vaccines was evaluated in mice. Initial studies showed that the purified LPS, which contained 0.14% protein as contaminant, had toxic effects in mice even at low levels. The mice exhibited toxic effects such as depression and ruffled hair coat after a few hours of inoculation and they survived if limited inoculation doses were used. It could be speculated that the protection afforded in mice immunised with LPS was not due to the LPS and the protection could be attributed to the contamination of proteins in the LPS extracts. Protective capacities of whole-cell killed vaccines grown under iron-regulated conditions were evaluated. Vaccines made from formalin-killed whole cells of P. multocida type 6:B grown under iron-restricted conditions were found to be superior in imparting protection to mice against experimental pasteurellosis than those grown under iron-repleted conditions. It could be speculated that some cell-associated antigens responsible for protective immunity were expressed better under iron-limiting conditions. The isolation and purification of outer membrane proteins (OMPs) in this study was from P. multocida grown under iron-restricted condition where a,a' -dipyridyl was used as the iron chelator. The extraction of OMP of P. multocida was carried out using Sarkosyl method. The final purified OMP was chosen for subsequent purification studies, as it contained less LPS and afforded 100% protection to immunised mice. The extracts were shown to have about 12 protein bands when electrophoressed on SDS-PAGE gels in which 33 kD and 37 kD proteins appeared as major OMPs of P. multocida with the 87 kD and 116 kD protein bands as next prominent ones. Active protection studies of purified proteins obtained after preparative electrophoresis llsing Prep Cell, cylindrical and stained gels have shown that proteins with MWs 29, 33 and 37 kD have the potential as subunit vaccines. Whereas, high MW proteins only afTorded up to 60% protection to the immunised mice. However, the Immune response of the target and laboratory animals was different as judged by comparative immunoblotting. Almost all the antibodies of mice and cattle antiserum reacted to 29, 33, 37, 52, 71, 87 and 116 kD proteins except 33 kD protein for cattle antiserum. It showed that the mice immune response is very similar to the cattle. Mice immunised with purified 29 kD alone was shown to afford a lower protection. When it was excised, electro-eluted then rerun on mini SDS-PAGE, the 29 kD protein produced a ladder form of protein bands of MW 29, 37 and 47 kD. It was speculated that the 29 kD protein is a monomeric form of the protein H of P. multocida and the 37 kD protein is a trimer. Thus, the trimeric form with MW 37 kD protein could be an attractive vaccine candidate.